(3GdYQhS aj aVGFd jhe GdLeYIs - (3GdEjdGaj Gdbej, CHh eMeO, GHf GdQGRj, LYaQ Hf CMeO Hf Ydj, J b (B5 (3g`s ((3MSf Hf YHO GdgGOj Hf ehSi GdehShj GdNQSGfjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3bGd GdeUfa SFdJ CWGd Gddg HbGAc gd NU jhe GdLeYI HYHGOI Shi CjGe GdCSHhY GYde Ydece Gddg GdNjQ Cf Gddg NU jhe GdLeYI HNUGd LeI (B...s
(3BNQgG (B:s
.. (3abO dZi hef dZi adG LeYI dg Yf GdCUHZ Hf fHGJI Yf Ydj Ydjg GdSdGe bGd EPG bGd GdQLd jhe GdLeYI eg adG UdGI dg (B. (3Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1\486s
(3GdPQjYI (B15- 184 (1633)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs